Kesakralan Syair dalam Masyarakat Pesantren - Itmam Muhammad (Pusat Studi Pesantren dan Pemberdayaan Masyarakat, LPPM, Universitas Brawijaya, 2024)
Pesantren (Islamic boarding schools) are educational institutions in Indonesia deeply connected to Islamic scholarship and their unique cultural traditions. One of the enduring cultural elements in pesantren is the use of syair (Islamic poetry). Within pesantren communities, syair holds a distinctive sacredness. This sacredness can be analyzed using Emile Durkheim's theory of societal sacrality. Through this analysis, the patterns of sacrality constructed by pesantren communities in relation to syair can be observed. Two patterns of syair sacrality emerge within pesantren communities: as an act of worship and as a medium for the transmission of knowledge.